PKB Performance on Increasing Active Family Planning Participants during the Covid 19 Pandemic - Sri Wardani; Afrizal Afrizal; Hazni Chairina (Science Midwifery, 2022)
Family Planning Extension (PKB) performance in the field has not been optimal, there are many obstacles in carrying out tasks in the field, where the Covid 19 pandemic condition is difficult for field officers to go directly to the community, limitations to socializing and meeting the community directly as well as limitations in getting information through information technology, there are people lack of technology mastery and even information network problems and the limitations of PKB in using IT-based information technology. Active family planning participants in Riau Province have fluctuated in the last three years. The type of research is mixed methods (quantitative and qualitative), the sample obtained is 76 people (total sampling), 25 informants are opened. The research instruments were questionnaires and in-depth interviews. The data were analyzed using univariate and triangulated data. The results showed that the performance of PKB was improved from good competence (70.3%), high motivation (50%), good communication (78.4%), good work discipline (64.9%), good work quality (51.4%), good counseling (100%), good improvement (66.2%), good work design (59.5%), good superior leadership (54.1%), good reward system ( 75,7%), good stake holder support (98,6%), active family planning participants increased (56.8%). It is recommended to improve performance through increasing training/workshops both in quantity and quality, increasing the budget for activities, awarding certificates and prizes, adding PKB personnel with a 1:2 ratio, increasing monitoring and evaluation activities, as well as increasing PPKBD/Poktan coaching with meetings. direct or virtual, strengthen synergy with cross-sectors, and increase advocacy with relevant policy makers.